ANALISIS PERSEDIAAN BAHAN BAKU PADA USAHA KECIL MENENGAH PRODUK ROTI (STUDI KASUS UD NABILA DI DESA KALASEY, KECAMATAN MANDOLANG) - Sheila G., Kaluntas; Noortje M. Benu; Yolanda P. I. Rori (AGRI-SOSIOEKONOMI, 2016)
The aimed of the study to analyzed the supply of raw material of bread at UD Nabila more specifically the raw material of the flour, sugar, butter and eggs. This study was conducted for two months, since January 2016 until February 2016. The data used in this research are secondary data, the data obtained from UD Nabila and primary data by interviews to the owner of UD Nabila. The analysis used in this research used EOQ (Economic Order Quantity) to know when to make a reservation and determine amount to reserve. Based on the results of this research at UD Nabila, it can be concluded that in determining the purchase of a raw material UD Nabila, don’t have the good inventory management of raw recipes. UD Nabila has not been able to calculate the optimal purchase of raw material, which is the purchase of raw material UD Nabila is more than the use of raw recipes, it causing profuse costs.*ls*